Single-incision laparoscopic partial splenectomy for benign pediatric splenic tumors: a retrospective comparative study - Tang, Ran; Wei, De-Cheng; Zhou, Cheng-Xiao; Li, Zhong-Ce; Bian, Jian; Qi, Shi-Qin (Frontiers in Pediatrics, 2025)
BackgroundThe indications for laparoscopic partial splenectomy (LPS) in pediatric benign splenic tumors are well established, but concerns remain regarding its technical complexity and potential complications. This study aimed to evaluate the safety and outcomes of single-incision LPS (SILPS).MethodsA retrospective analysis was conducted on 22 children who underwent SILPS from July 2021 to April 2024, compared with 25 patients who received laparoscopic total splenectomy (TS). Clinical characteristics, operative details, and postoperative outcomes were assessed.ResultsSILPS patients had comparable operative time, blood loss, and hospital stay to those in the TS group. However, SILPS was associated with significantly lower rates of postoperative thrombocytosis and leukocytosis. No major perioperative complications were observed.ConclusionSILPS is a safe and effective spleen-preserving technique for pediatric benign splenic tumors, offering reduced hematologic complications without increasing surgical risks. It is technically demanding and requires experienced laparoscopic skills and proper patient selection.